Hell and the Image of God - McIntosh, C. A. (Philosophia Christi, 2024)
I argue that we can cease to be human by losing the imago Dei. Such a view has profound implications for how we understand hell, offering a fresh perspective on the debate between traditionalists, annihilationists, and universalists.